Who is responsible for asymmetric fuel price adjustments? An application of the threshold cointegrated VAR model - Emilia Gosińska; Katarzyna Leszkiewicz-Kędzior; Aleksander Welfe (Baltic Journal of Economics, 2020)
The purpose of the paper is to test the hypothesis about asymmetric price transmission between the fuel markets. The distribution chain is considered at three levels: the European wholesale market, the domestic wholesale market, and the domestic retail market. It is shown that between the European and domestic wholesale markets fuel prices adjust symmetrically and asymmetrically between the domestic wholesale market and the retail market. This finding confirms that the most probable cause of asymmetric price adjustments (especially in new EU member states) is the behaviour of petrol stations and not of oil companies. The empirical analysis is conducted using an appropriately modified Hansen-Seo method. The procedure, which has until recently been used to estimate bivariate threshold models, prevents the presence of the constant in the cointegrating vector entailing the risk of severe distortion of the estimation results. Moreover, the interpretation of a dummy variable present in the CVAR equation as a result of a data generating process distortion is limited by its presence in the cointegration space.
Keywords: C10; C32; D40; Q40; 330; Threshold cointegration; threshold cointegrated VAR; modified Hansen-Seo method; fuel pricing; asymmetric price adjustments